ANALISIS PENGARUH FAKTOR INKLUSI KEU-ANGAN DAN MAKRO EKONOMI TERHADAP KETIMPANGAN PENDAPATAN DI 8 NEGARA MID-DLE INCOME KAWASAN ASEAN PADA TAHUN 2013-2019 - Rizkianda, Kinan Muhammad; Wiguna, Atu Bagus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The level of success of a country in the process of economic development is determined by the creation of a stable financial system that can be accessed by all levels of society. The implementation of the Financial Inclusion program in ASEAN countries is in accordance with the SDGs target that is being carried out where the aspect of reducing income inequality is at 10 points out of 17 global goals by maintaining population income growth which is below 40% of the population at a higher than average level. national. This study aims to identify how big the impact of financial inclusion and macroeconomic factors on income inequality in eight middle-income countries in Southeast Asia. The period of this research is from 2013 to 2019. In this research, the researcher uses panel data regression analysis. The results of this study indicate that financial inclusion has an influence on income inequality. Of the three financial inclusion variables, all three have a significant negative effect on income inequality, namely the variables of penetration, availability, and use. Meanwhile, macroeconomic variables consisting of economic growth and poverty have a positive and significant effect on income inequality. In addition, the inflation variable also does not have a significant effect on income inequality.